Power Quality Experimental Analysis on Rural Home Grid-Connected PV Systems - Rita Jorge Cerqueira Pinto; Sílvio José Pinto Simões Mariano; Maria do Rosário Alves Calado (International Journal of Photoenergy)
Microgeneration is the small-scale generation of heat or electric power or both, by individuals or buildings to meet their own needs. Recently, microgeneration is being regarded as a means to decentralize the power production of renewable energies, reducing the impacts on the grid caused by unexpected energy demands. Given the increase in microgeneration facilities, determining the quantity of energy produced and the power quality assumes growing importance in low, medium, or high voltage facilities. This paper presents a power quality analysis of two different facilities with photovoltaic generation localized in a rural area of Portugal, describing the voltage and frequency behaviour, the harmonic contents, and the total harmonic distortion. Statistical data are presented regarding the number of voltage events and occurrence of dips and swells in both facilities as a percentage of rated voltage. We conclude that some PV systems can severely affect voltage quality, forcing the grid to work at and even above the maximum voltage standard limit.